PENERAPAN METODE SIMULASI UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PKN SISWA DI SD NEGERI 187/IV KOTA JAMBI - Juniar Siregar (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2016)
This study presents a research report on using simulation method to improve the activity and the students’ learning result improving students’ Learning results on PKn. The objective was to find out whether the activity and the students’ learning result improved when they are taught by using Video. It was conducted using classroom action research method. The subject of the study was the Grade IV students of SDN 187/IV Kota Jambi which is located on Jln. Adi Sucipto RT 05 Kecamatan Jambi Selatan, and the number of the students were 9 persons. The instruments used were test as quantitative data and observation, interview, and questionnaire were used as qualitative data. In analyzing the data, the mean of the students’ score for the on first cycle was 74.11 and the mean on cycle two was 78.00 and the mean of the third cycle was 84.7. Then it can be concluded that the use of simulation as a learning method can improve the students’ activity and students’ learning result. It is suggested that teachers should apply simulation method as a learning method to improve students’ activity and students’ learningresult on PKn.Keywords : PKn, students’ activity, students’ learning results, simulation method